Spherical Oligo-Silicic Acid SOSA Disclosed as Possible Endogenous Digitalis-Like Factor - Kerek, Franz; Voicu, Victor A. (Frontiers in Endocrinology, 2015)
Na+/K+-ATPase is a membrane ion-transporter protein, specifically inhibited by digitalis glycosides used in cardiac-therapy. The existence in mammals of some endogenous digitalis-like factors (EDLF) as presumed ATPase ligands is generally accepted. But the chemical structure of these factors remained elusive because no weighable amounts of pure EDLF have been isolated. Recent high resolution crystal structure data of Na+/K+-ATPase have located the hydrophobic binding pocket of the steroid glycoside ouabain. Our recently disclosed spherical oligo-silicic acids (SOSA) fulfill the main criteria to be identified with the presumed EDL factor. SOSA was found as a very potent inhibitor of the Na+/K+-ATPase, Ca2+-ATPase, H+/K+-ATPase and of K-dp-ATPase, with IC50 values between 0.2-0.5µg/ml. These findings are even more astonishing while so far, neither mono silicic acid nor its poly-condensed derivatives have been remarked biologically active. With the diameter ϕ between 1 - 3nm, SOSA still belong to molecular species definitely smaller than silica nano-particles with ϕ >5nm. In SOSA molecules almost all Si-OH bonds are displayed on the external shell which facilitates the binding to hydrophilic ATPase domains. SOSA is stable for long-term in solution but is sensitive to freeze-drying which could explain the failure of countless attempts to isolate pure EDLF. There is a strong resemblance between SOSA and vanadates, the previously known general inhibitors of P-type ATPases. SOSA may be generated endogenously by spherical oligomerization of the mono-silicic acid ubiquitously present in animal cells and fluids. Based on the finding that the SOSA structure is sensitive to the concentration and nature of the cationic species a presumably archaic mechanism to regulate the activity of the ATPase pumps is proposed.